2014
DOI: 10.1161/hypertensionaha.114.03315
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Microvascular Endothelial Type B Endothelin Receptor Is a Central Vascular Mechanism in Hypertensive Pregnancy

Abstract: Preeclampsia is a pregnancy-related disorder characterized by hypertension (HTN) with unclear mechanism. Studies have shown endothelial dysfunction and increased endothelin-1 (ET-1) levels in hypertensive-pregnancy (HTN-Preg). ET-1 activates endothelin receptor type-A (ETAR) in vascular smooth muscle to induce vasoconstriction, but the role of vasodilator endothelial ETBR in the changes in blood pressure (BP) and vascular function in HTN-Preg is unclear. To test if downregulation of endothelial ETBR expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
89
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(100 citation statements)
references
References 44 publications
11
89
0
Order By: Relevance
“…Expression and activity of endothelial ET B receptors were reduced in rats with preeclampsia-like features (ie, hypertension, intrauterine growth restriction, proteinuria, renal dysfunction) induced by surgical reduction of uterine blood flow as compared with sham controls. 63 Others have shown that contractile responses to inactive precursor big ET-1 were increased in mesenteric arteries from this experimental model and that inhibition of matrix metalloproteinase, an enzyme that catalyzes the conversion of big ET-1 to ET-1, abolished the enhanced contractile responses. 65 Collectively, studies on endothelium-derived constrictors suggest that TxA 2 and ET-1 contribute to maternal vascular dysfunction in women with preeclampsia and in animal models with experimental preeclampsia.…”
Section: Hypertensionmentioning
confidence: 60%
See 1 more Smart Citation
“…Expression and activity of endothelial ET B receptors were reduced in rats with preeclampsia-like features (ie, hypertension, intrauterine growth restriction, proteinuria, renal dysfunction) induced by surgical reduction of uterine blood flow as compared with sham controls. 63 Others have shown that contractile responses to inactive precursor big ET-1 were increased in mesenteric arteries from this experimental model and that inhibition of matrix metalloproteinase, an enzyme that catalyzes the conversion of big ET-1 to ET-1, abolished the enhanced contractile responses. 65 Collectively, studies on endothelium-derived constrictors suggest that TxA 2 and ET-1 contribute to maternal vascular dysfunction in women with preeclampsia and in animal models with experimental preeclampsia.…”
Section: Hypertensionmentioning
confidence: 60%
“…63 Pharmacological inhibition of ET A reduces preeclampsia-like symptoms in various models of experimental preeclampsia, indicating that the ET-1 contribution to preeclampsia is ET A dependent. 64 ET B receptors are also involved in experimental preeclampsia.…”
Section: Hypertensionmentioning
confidence: 99%
“…6 and Table 1). DPN maximum relaxation and EC 50 were not different in all vessels of pregnant versus virgin rats. G1-induced maximum relaxation was only greater in the aorta of pregnant versus virgin rats (Fig.…”
Section: Bp Plasma E 2 Body Weight and Tissue Weightmentioning
confidence: 67%
“…We assessed if pregnancy-induced changes in vascular ERs could affect vascular function. In blood vessels isolated from virgin rats and precontracted with Phe, all ER agonists caused greater maximum relaxation with no difference in EC 50 in the mesenteric and renal artery versus the aorta and carotid artery (Fig. 6 and Table 1).…”
Section: Bp Plasma E 2 Body Weight and Tissue Weightmentioning
confidence: 90%
See 1 more Smart Citation